A modified multifunctional calcium carbonate and preparation method thereof

By adding specific components to the calcium carbonate powder, a modified multifunctional heavy calcium carbonate powder was prepared, which solved the problem of single function of the existing calcium carbonate powder and achieved versatility and performance improvement.

CN119307119BActive Publication Date: 2025-04-22SHANDONG JINSHENG NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411858039.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-22
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing calcium carbonate powder has a single function and is difficult to meet the multiple requirements in its use field.

Method used

A modified multifunctional heavy calcium carbonate powder was prepared by adding components such as coupling agent, α-linolenic acid polyhydroxy derivative, 9,10-dihydro-9-oxa-10-phosphophenophen-10-oxide derivative, rosmarinic acid and its derivatives, chitosan/chitooligosaccharide derivatives and titanium dioxide.

Benefits of technology

The versatility of calcium carbonate powder is achieved, the viscosity of the filling system is reduced, and the mechanical properties, antibacterial properties, oxidation resistance and flame retardant properties of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307119B_ABST
    Figure CN119307119B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of calcium carbonate powder modification, and discloses a modified multifunctional calcium carbonate and a preparation method thereof. The modified multifunctional calcium carbonate comprises the following components in proportion by weight: 100 parts of calcium carbonate, 0.3-0.5 parts of coupling agents, 0.4-0.7 parts of alpha-linolenic acid polyhydroxy derivatives, 0.5-1.0 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives, 0.05-0.15 parts of rosmarinic acid and derivatives thereof, 0.2-0.35 parts of chitosan / chitosan oligosaccharide derivatives, and 0.2-0.3 parts of titanium dioxide. The modified multifunctional calcium carbonate has multiple functions, a wide range of applications, and moderate costs. When used for filling different plastic materials, the modified multifunctional calcium carbonate has the advantages of improved physical and mechanical properties, reduced flame retardant costs, increased fluidity, and the like, and can also produce antibacterial, anti-aging, deodorizing, and the like functions. When used for adhesive filling, the modified multifunctional calcium carbonate has the advantages of high extrudability of the finished adhesive, high mechanical properties, low sag, and the like, and is a rare multifunctional filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of calcium carbonate powder modification, in particular to a modified multifunctional heavy calcium carbonate powder and a specific preparation method of the modified multifunctional heavy calcium carbonate powder. Background Art

[0002] As the most effective means to reduce costs, calcium carbonate powder filling modification has been adopted in the field of polymer material modification. Calcium carbonate has become the darling of polymer modification applications due to its high whiteness, low price and non-toxicity. As technical developers, we always expect that when calcium carbonate is filled in polymer materials, in addition to reducing costs, it can also contribute to improving the performance of polymer materials. Filler modification technology came into being.

[0003] Due to the different technical requirements and purposes of modified polymer materials, the requirements for filler modification also vary greatly. However, the current calcium carbonate powder generally has a single function and is difficult to meet the many requirements of its application field. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a modified heavy calcium carbonate with multiple application functions.

[0005] In order to solve the above technical problems, the technical solution of the present invention is: a modified multifunctional calcium carbonate, comprising the following components in proportion by weight:

[0006] 100 parts of calcium carbonate, 0.3-0.5 parts of coupling agent, 0.4-0.7 parts of α-linolenic acid polyhydroxy derivatives, 0.5-1.0 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives, 0.05-0.15 parts of rosmarinic acid and its derivatives, 0.2-0.35 parts of chitosan / chitosan oligosaccharide derivatives, and 0.2-0.3 parts of titanium dioxide.

[0007] As a preferred technical solution, the particle size of the calcium carbonate tested by the OMEC particle size tester is D 50 ≦4.152µm, D 97 Heavy calcium carbonate ≦13.116µm;

[0008] The heavy calcium carbonate is obtained by grinding with a vertical mill;

[0009] The heavy calcium carbonate is added with 1-1.5‰ grinding aid dispersant during grinding;

[0010] The grinding aid dispersant is one of maleic acid-acrylic acid copolymer sodium salt, sodium dodecyl sulfate, and sodium hexametaphosphate;

[0011] The obtaining of the heavy calcium carbonate comprises the following steps:

[0012] SP A1 , using tap water to wash the calcium carbonate ore to remove the silt and humus in the calcium carbonate ore;

[0013] SP A2 , crushing the calcium carbonate ore, and after the first and second crushing processes, the maximum size of the calcium carbonate ore after crushing is no more than 30 mm;

[0014] SP A3 , take 20 to 25 times the mass of the grinding aid dispersant and add it to the grinding aid dispersant to prepare a dilute solution or emulsion, heat the grinding aid dispersant diluted with pure water, and control the heating temperature to 50 to 60° C.;

[0015] SP A4 3. Metering and conveying the crushed calcium carbonate ore using a vibrating screen;

[0016] SP A5 , using a metering pump to evenly spray the diluted and heated grinding aid dispersant onto the crushed calcium carbonate ore on the vibrating screen in a ratio that matches the mass of the calcium carbonate ore;

[0017] SP A6 , feeding the calcium carbonate ore sprayed with the grinding aid dispersant into the vertical mill for grinding;

[0018] SP A7 , setting the grinding process according to the particle size requirements of the heavy calcium carbonate to grind out powder that meets the particle size requirements;

[0019] SP A8 2. If the powder that meets the particle size requirements needs to be further classified, it will be sent to the next classification procedure. After the powder that meets the specified requirements is classified, it will be sent to the finished product warehouse; powder that does not need to be further classified will be directly sent to the finished product warehouse.

[0020] As a preferred technical solution, the coupling agent is one of distearoyloxyisopropyl aluminate, phosphate acyloxy isooctyl aluminate, anti-settling aluminate, isopropyl tris (dioctyl pyrophosphate acyloxy) titanate, di (dioctyl pyrophosphate acyloxy) glycolate titanate, di (dioctyl pyrophosphate acyloxy) oxoester titanate, aluminum-titanium composite coupling agent, aluminum zirconate coupling agent, or a combination of two of them in any ratio.

[0021] As a preferred technical solution, the structural formula of the α-linolenic acid polyhydroxy derivative is as follows:

[0022]

[0023] The structure of R1 is , or

[0024] .

[0025] As a preferred technical solution, the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative includes one of a 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing an epoxy group, a 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing a tung oil polyol group, or a 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing a siloxane group;

[0026] Wherein, the structural formula of the epoxy-containing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative is:

[0027]

[0028] The structural formula of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing tung oil polyol group is ,

[0029] The structural formula of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing a siloxane group is .

[0030] As a preferred technical solution, the rosmarinic acid and its derivatives are one of rosmarinic acid dodecanol ester, rosmarinic acid methyl ester or rosmarinic acid.

[0031] As a preferred technical solution, the chitosan / chitosan oligosaccharide derivative is one of chitosan o-oxy (meta-oxy or para-oxy) benzaldehyde Schiff base-polyamine ethyl-diethyl phosphate or chitosan oligosaccharide o-oxybenzaldehyde Schiff base-polyamine ethyl-diethyl phosphate.

[0032] As a preferred technical solution, the titanium dioxide is rutile nano titanium dioxide.

[0033] The present invention also discloses a method for preparing the modified multifunctional calcium carbonate, which is completed by using a weightless mixer, an auxiliary agent delivery system and a three-roller activation unit;

[0034] The auxiliary agent delivery system includes a liquid auxiliary agent delivery system and a solid auxiliary agent delivery system;

[0035] The liquid auxiliary agent delivery system includes two heating tanks, each of which is connected to a metering pump, each of which is connected to a liquid infusion tube, the other end of which is connected to a nozzle rod, a nozzle is installed on the nozzle rod, the nozzle rod is installed on the zero-gravity mixer, and a heating tube is installed in the heating tank;

[0036] The solid additive delivery system includes a variable frequency high-speed mixer and a buffer bin disposed below the discharge port of the variable frequency high-speed mixer, and a loss-in-weight scale is installed below the discharge port of the buffer bin;

[0037] The loss-in-weight scale comprises a silo and a barrel placed below the silo, a screw is installed in the barrel, the rear end of the screw extends out of the barrel and is connected to a power system, a discharge port is installed at the front end of the barrel, and the silo is connected to the discharge port of the buffer silo;

[0038] The three-roller activation unit includes an elevator, the discharge port of the weightless mixer is connected to the feed port of the elevator through auger 2, the discharge port of the elevator is connected to a raw material bin, the discharge port at the bottom of the raw material bin is connected to auger 1, the discharge port of the loss-in-weight scale is connected to auger 1, the discharge port of auger 1 is connected to the three-roller activator, the discharge port of the three-roller activator is connected to an induced draft fan, the discharge port of the induced draft fan is connected to a classifier through pipeline 1, the classifier is provided with upper and lower discharge ports, the upper discharge port of the classifier is connected to a bag filter through pipeline 4, the bag filter is connected to a corresponding finished product bin through pipeline 3 equipped with a Roots blower, and the lower discharge port of the classifier is connected to the auger 1 through pipeline 2.

[0039] As a preferred technical solution, the modified multifunctional calcium carbonate comprises the following steps:

[0040] SP B1 , raising the temperature of the zero-gravity mixer to 80-90° C., and keeping the temperature for 30 minutes after reaching the set temperature;

[0041] SP B2 , add the coupling agent into one of the heating tanks, when the coupling agent is liquid and the kinematic viscosity at 25°C is not greater than 80 mm 2 / s, no heating is required, when the kinematic viscosity at 25℃ is greater than 80mm 2 / s, the liquid coupling agent needs to be heated to reduce viscosity, and the heating temperature is controlled at a heating temperature at which the kinematic viscosity of the liquid coupling agent is between 50 and 80 mm 2 / s; when the coupling agent is solid, the solid coupling agent needs to be heated to melt and reduce viscosity, and the heating temperature is controlled at a heating temperature at which the kinematic viscosity of the solid coupling agent after melting is 50~80mm 2 / s;

[0042] SP B3 , adding the α-linolenic acid polyhydroxy derivative into another heating tank, and heating the heating tank at a heating temperature of 70 to 85° C.;

[0043] SP B4 , the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, the rosmarinic acid and its derivatives, the chitosan / chitosan oligosaccharide derivatives, and the titanium dioxide are weighed according to the proportion of each component in the formula, and are put into the variable frequency high-speed mixer to form a mixed solid additive, and 5 times the total amount of the mixed solid additive is added through step SP A8 The prepared heavy calcium carbonate is used to amplify the mass of the mixed solid additive;

[0044] SP B5 , start the variable frequency high-speed mixer to mix materials, the frequency of the variable frequency high-speed mixer is 10-12.5 Hz, adjust its frequency to 25-27 Hz after mixing for 5-7 minutes, continue mixing for 2-3 minutes and then discharge the materials, discharge the enlarged auxiliary agent into the buffer bin, and put it into the silo on the loss-in-weight scale through the buffer bin;

[0045] SP B6 , start the zero-gravity mixer, and pass step SP A8 The prepared heavy calcium carbonate is metered into the zero-gravity mixer, and the speed of the zero-gravity mixer is adjusted to 50-70 rad / min;

[0046] SP B7 , after the temperature of the heavy calcium carbonate material in the zero-gravity mixer reaches 80° C., start the metering pump corresponding to the heating tank with a built-in coupling agent, adjust the output of the metering pump, and spray the coupling agent matching the mass of the heavy calcium carbonate onto the heavy calcium carbonate material in the zero-gravity mixer. The coupling agent addition time is controlled within 45 to 60 seconds, and the mixing is continued for 10 to 12 minutes;

[0047] SP B8 , starting the metering pump corresponding to the heating tank containing the α-linolenic acid polyhydroxy derivative, adjusting the output of the metering pump, spraying the α-linolenic acid polyhydroxy derivative matching the mass of the heavy calcium carbonate onto the heavy calcium carbonate material in the zero-gravity mixer, controlling the addition time of the α-linolenic acid polyhydroxy derivative to be completed within 45 to 60 seconds, and continuing mixing for 20 to 25 minutes;

[0048] SP B9, discharging the heavy calcium carbonate mixture containing the coupling agent and the α-linolenic acid polyhydroxy derivative, and transferring it from the zero-gravity mixer to the raw material bin via the auger 2 and the elevator;

[0049] SP B10 , starting the auger 1 to transfer the heavy calcium carbonate mixture from the raw material bin to the auger 1 in a quantitative manner;

[0050] SP B11 , starting the loss-in-weight scale, feeding the mixed solid additives magnified by the heavy calcium carbonate into the auger according to a proportion, and mixing them with the heavy calcium carbonate mixed material transferred from the raw material bin to form a final mixed material;

[0051] SP B12 , starting the three-roller activation unit, and the auger 1 delivers the final mixed material into the three-roller activation unit through the discharge port for continuous mixing and activation;

[0052] SP B13 , starting the induced draft fan, and the final mixed material activated by the three-roller activation machine enters the classifier through pipeline 1 under the action of the induced draft fan;

[0053] SP B14 , the mixed and activated mixed materials entering the classifier are classified, and the qualified powders enter the bag filter from the upper discharge port of the classifier through the pipeline 4, and the powders agglomerated during the activation process enter the auger 1 from the lower discharge port of the classifier through the pipeline 2, and return to the three-roller activation unit for further activation and crushing;

[0054] SP B15 , the mixed and activated mixed material entering the bag filter is cooled and then enters the finished product bin through pipeline three;

[0055] SP B16 , packaging the materials in the finished product warehouse to form a modified multifunctional calcium carbonate finished product.

[0056] Due to the adoption of the above technical solution, the present invention has the following beneficial effects:

[0057] ① The use of the coupling agent in the present invention allows the bipolar active groups in the coupling agent to chemically or physically combine with the hydroxyl groups (-OH) on the surface of the heavy calcium carbonate, and at the same time, cooperate with the hydroxyl groups (-OH) contained in the α-linolenic acid polyhydroxy derivative to participate in the reaction of the hydroxyl groups (-OH) on the surface of the heavy calcium carbonate. The film-forming function of the aluminate coupling agent in the coupling agent on the surface of calcium carbonate or the function of the titanate coupling agent in the coupling agent to rapidly change the surface energy and greatly reduce the viscosity of the system due to the large number of carbon atoms, and the α-linolenic acid polyhydroxy derivatives to separate the molecular distance, effectively reduce the viscosity of the filling system when the modified multifunctional heavy calcium carbonate is used.

[0058] ② The α-linolenic acid polyhydroxy derivatives, the rosmarinic acid and its derivatives, the chitosan / chitosan oligosaccharide derivatives, and the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives used in the present invention all have structures of long-chain compounds containing polyhydroxyl groups (-OH) or amine groups (-NH2) or imino groups (-NH-). The α-linolenic acid polyhydroxy derivatives, the chitosan / chitosan oligosaccharide derivatives, and the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives are long-chain compounds. When they are used for adhesive filling, the α-linolenic acid polyhydroxy derivatives, the chitosan / chitosan oligosaccharide derivatives, the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives are The long chains of the 0-phosphaphenanthrene-10-oxide derivatives are swollen, and the swollen long chains are entangled with each other. When the hydroxyl (-OH) or amine (-NH2) or imino (-NH-) on the structure of the tung oil polyol-based 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives in the α-linolenic acid polyhydroxy derivatives, the rosmarinic acid and its derivatives, the chitosan / chitosan oligosaccharide derivatives and the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives are dissolved in an organic system, they are gelled due to the action of hydrogen bonds to form a thixotropic network structure. These network structures or the entangled long chains are destroyed under the action of shear force, which is manifested as a decrease in viscosity, so that the system recovers good fluidity. When the shear force is eliminated, the three-dimensional structure will recover by itself to increase the viscosity, showing thixotropy.

[0059] ③ The phosphorus (P), nitrogen (N) or silicon (Si) contained in the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative and the chitosan / chitosan oligosaccharide derivative respectively in the present invention is a component of the flame retardant, and the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, the chitosan / chitosan oligosaccharide derivative and the rosmarinic acid and its derivatives all contain a benzene ring structure that can form carbon, and phosphorus (P) and nitrogen (N) are also synergists of halogen element flame retardants. At the same time, the coupling agent used in the present invention also contains aluminum (Al) and phosphorus (P) with flame retardant function, which is helpful to reduce the comprehensive cost of the formula when designing the flame retardant material formula filled with the modified multifunctional heavy calcium carbonate.

[0060] ④ In the present invention, the rosmarinic acid and its derivatives, the chitosan / chitosan oligosaccharide derivatives, and the titanium dioxide all have antibacterial functions. The three are used in combination to make the polymer material filled with the modified multifunctional heavy calcium carbonate have antibacterial properties.

[0061] ⑤ In the present invention, the rosmarinic acid and its derivatives and the titanium dioxide both have antioxidant effects, and the combination of the two improves the aging resistance of the polymer material filled with the modified multifunctional heavy calcium carbonate.

[0062] ⑥ In the present invention, the α-linolenic acid polyhydroxy derivative, the chitosan / chitosan oligosaccharide derivative, and the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative are long-chain compounds. When the modified calcium carbonate is used for filling, the long-chain structures of the α-linolenic acid polyhydroxy derivative, the chitosan / chitosan oligosaccharide derivative, and the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative are entangled with the matrix material, wherein the α-linolenic acid polyhydroxy derivative contains a hydroxyl group (-OH), the chitosan / chitosan oligosaccharide derivative contains an ethoxy group (-OCH2CH3), and the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative contains a hydroxyl group (-OH) or an ethoxy group (-OCH2CH3) or an epoxy group (-OCH2CH3) in its structure. ), the rosmarinic acid and its derivatives contain hydroxyl (-OH) and / or methoxy (-OCH3) in their structures, and the hydroxyl (-OH), methoxy (-OCH3), ethoxy (-OCH2CH3) or epoxy ( ) can produce a grafting or cross-linking reaction with the matrix material when conditions permit, and the use of the coupling agent helps to improve the mechanical properties of the modified multifunctional heavy calcium carbonate filling system.

[0063] ⑦ In the present invention, the chitosan / oligochitosan derivatives, the rosmarinic acid and its derivatives, and the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives all contain rigid benzene rings, which, when combined with rigid inorganic ion calcium carbonate, help improve the rigidity of the multifunctional heavy calcium carbonate filling system using this modification.

[0064] ⑧ In the present invention, the rosmarinic acid and its derivatives have a special fragrance, which helps to improve the odor of the modified multifunctional heavy calcium carbonate filling system. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] The following drawings are only intended to illustrate and explain the present invention, and are not intended to limit the scope of the present invention.

[0066] in:

[0067] Figure 1 It is a simplified view of the main viewing direction of the equipment used in the preparation method of the embodiment of the present invention;

[0068] Figure 2 It is a simplified top view of the equipment used in the preparation method of the embodiment of the present invention;

[0069] Figure 3 yes Figure 2 Simple view in the middle AA direction;

[0070] Figure 4 yes Figure 3 Simple view of the middle BB direction;

[0071] In the figure: 1-raw material warehouse; 2-elevator; 3-loss-in-weight scale; 4-raw material feeding port; 5-additive feeding port; 6-auger one; 7-weightless mixer; 8-auger two; 9-three-roller activation unit; 901-first three-roller activator; 902-second three-roller activator; 903-third three-roller activator; 10-induced draft fan; 11-pipeline one; 12-pipeline two; 13-classifier; 14-Roots blower; 15-bag filter; 16-air shutoff device; 17-pipeline three; 18-finished product warehouse; 19-variable frequency high mixer; 20-buffer warehouse; 21-heating tank one; 22-metering pump one; 23-infusion pipe one; 24-nozzle rod; 25-nozzle; 26-heating tank two; 27-metering pump two, 28-infusion pipe two; 29-heating pipe; 30-pipeline four. DETAILED DESCRIPTION

[0072] The present invention is further described below in conjunction with the accompanying drawings and examples. In the following detailed description, certain exemplary embodiments of the present invention are described only by way of illustration. Needless to say, those of ordinary skill in the art will recognize that the described embodiments may be modified in various ways without departing from the spirit and scope of the present invention. Therefore, the drawings and description are illustrative in nature and are not intended to limit the scope of protection of the claims.

[0073] A modified multifunctional calcium carbonate comprises the following components in proportion by weight: 100 parts of calcium carbonate, 0.3-0.5 parts of coupling agents, 0.4-0.7 parts of alpha-linolenic acid polyhydroxy derivatives, 0.5-1.0 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives, 0.05-0.15 parts of rosmarinic acid and its derivatives, 0.2-0.35 parts of chitosan / chitosan oligosaccharide derivatives and 0.2-0.3 parts of titanium dioxide.

[0074] The particle size of the calcium carbonate measured by the OMEC particle size tester is D 50 ≦4.152µm, D 97 Heavy calcium carbonate with a particle size of ≦13.116µm. The heavy calcium carbonate is obtained by grinding with a vertical mill, and 1 to 1.5‰ of a grinding aid dispersant is added to the heavy calcium carbonate during grinding. The grinding aid dispersant is one of maleic acid-acrylic acid copolymer sodium salt, sodium dodecyl sulfate, and sodium hexametaphosphate.

[0075] The obtaining of the heavy calcium carbonate comprises the following steps:

[0076] SP A1 , using tap water to wash the calcium carbonate ore to remove the silt and humus in the calcium carbonate ore.

[0077] SP A2 , crushing the calcium carbonate ore, and after the first crushing and the second crushing process, the maximum size of the calcium carbonate ore after crushing is no more than 30 mm.

[0078] SP A3 , take 20 to 25 times the mass of the grinding aid dispersant and add it to the grinding aid dispersant to prepare a dilute solution or emulsion, heat the grinding aid dispersant diluted with pure water, and control the heating temperature to 50 to 60°C.

[0079] SP A4 , the crushed calcium carbonate ore is measured and transported using a vibrating screen.

[0080] SP A5, using a metering pump to evenly spray the diluted and heated grinding aid dispersant onto the crushed calcium carbonate ore on the vibrating screen in a ratio that matches the mass of the calcium carbonate ore;

[0081] SP A6 , sending the calcium carbonate ore sprayed with the grinding aid dispersant into the vertical mill for grinding.

[0082] SP A7 , setting the grinding process according to the particle size requirements of the heavy calcium carbonate to grind out powder that meets the particle size requirements.

[0083] SP A8 2. If the powder that meets the particle size requirements needs to be further classified, it will be sent to the next classification procedure. After the powder that meets the specified requirements is classified, it will be sent to the finished product warehouse; powder that does not need to be further classified will be directly sent to the finished product warehouse.

[0084] The grinding dispersing mechanism of the grinding aid dispersant is as follows: when the grinding aid dispersant sprayed on the crushed stone is ground with the crushed stone at the same time, the grinding aid dispersant will be adsorbed on the crushed stone, and with the progress of grinding, it will be adsorbed on the new surface of the crushed ore, reducing the external stress required for crack expansion when the crushed ore is broken and ground to smaller particles, thereby promoting the expansion of cracks. In the grinding process, due to the action of external mechanical forces, the particles absorb mechanical energy, the specific surface area changes first, and the surface energy also changes at the same time. With the increase of the specific surface area and specific surface energy of the particles, the bond force between adjacent atoms breaks, and this bond force is naturally activated on the new surface formed after crushing. In the early stage of crushing, the new surface tends to be generated along the original fine cracks or weakened parts inside the particles, so the bond force on the new surface is small; with the extension of the crushing time and the reduction of the particle size, the unsaturation degree on the surface increases, and the increase of surface energy and mechanical activation make the added grinding aid dispersant molecules spontaneously perform physical adsorption and chemical adsorption on the new surface, among which the chemical adsorption effect is more prominent. Since the adsorption of these molecules reduces the surface energy and generates steric hindrance, it can prevent the aggregation and recrystallization of particles, and finally play the role of dispersion and grinding. The reason for heating and diluting the grinding aid dispersant is that heating can more easily stimulate the molecular motion activity of the grinding aid dispersant, making the grinding aid dispersant more easily adsorbed on the surface of the ore.

[0085] The coupling agent is one of distearyloxyisopropylaluminate, phosphate acyloxyisooctanolaluminate, anti-settling aluminate, isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, di(dioctyl pyrophosphate acyloxy)hydroxyacetate titanate, di(dioctyl pyrophosphate acyloxy)oxyester titanate, aluminum-titanium composite coupling agent, aluminum zirconate coupling agent, or any combination of two in any ratio. The specific coupling mechanism of the coupling agent is a well-known technology and will not be repeated here. The above-mentioned coupling agents contain elements such as aluminum (Al) and phosphorus (P), and the elements such as aluminum (Al) and phosphorus (P) are flame retardant elements themselves and have the effect of flame retardant enhancement. At the same time, the aluminate coupling agent in the coupling agent has a film-forming function and the titanate coupling agent in the coupling agent has a large number of carbon atoms, which rapidly changes the surface energy, can greatly reduce the viscosity of the system, and has the effect of improving fluidity.

[0086] The structural formula of the α-linolenic acid polyhydroxy derivative described in this embodiment is as follows:

[0087] The structure of R1 is , or

[0088] .

[0089] The α-linolenic acid polyhydroxy derivatives are all polyhydroxy (-OH) structure compounds, and the heavy calcium carbonate is an alkaline compound containing a hydroxyl (-OH) structure on the surface. Under the action of high temperature and stirring shear force, some of the hydroxyl (-OH) in the α-linolenic acid polyhydroxy derivatives react with the hydroxyl (-OH) on the surface of the heavy calcium carbonate to form an ether bond (-O-), thereby forming a strong link. At the same time, the α-linolenic acid polyhydroxy derivatives are long-chain structures, and the structure also contains double bonds. When used for filling and modification, these long chains are entangled with the base material. For example, when plastic filling is performed, when the plastic base material contains a group that is easily broken by high temperature or hydrolysis, the hydroxyl (-OH) or double bond of the α-linolenic acid polyhydroxy derivative that does not participate in the reaction of the hydroxyl (-OH) on the surface of the heavy calcium carbonate combines with the base material when the base material breaks the chain, thereby playing the role of end group blocking, thereby improving the mechanical properties of the material.

[0090] When applied to adhesives, the hydroxyl groups (-OH) of the α-linolenic acid polyhydroxy derivatives form a network structure through hydrogen bonds. At the same time, the long-chain α-linolenic acid polyhydroxy derivatives are swelled to form mutually entangled structures, thereby having the characteristic of improving the thixotropy of the blending system.

[0091] The 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative includes one of a 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing an epoxy group, a 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing a tung oil polyol group, or a 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing a siloxane group;

[0092] Wherein, the structural formula of the epoxy-containing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative is:

[0093] ,

[0094] The structural formula of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing tung oil polyol group is ,

[0095] The structural formula of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing a siloxane group is .

[0096] The mechanism of action of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative is as follows: ① The phosphorus (P) content of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing an epoxy group is 4.51%, the phosphorus (P) content of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing a tung oil polyol group is 7.47%, the phosphorus (P) content of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing a siloxane group is 7.79%, the silicon (Si) content is 7.04%, and the nitrogen (N) content is 3.52%, and phosphorus (P), silicon (Si) and nitrogen (N) are all flame retardant components in the flame retardant, and at the same time, the 9, The 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative also contains a benzene ring structure with a carbon-forming function, so the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative has a certain flame retardant effect when applied to plastic materials. In addition, phosphorus (P) and nitrogen (N) are also flame retardant synergists of halogen flame retardants, so the amount of flame retardants in flame-retardant plastic materials can be reduced, and the cost of flame retardant materials can be correspondingly reduced; ② The 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative contains a rigid structure benzene ring in the molecular chain, so it has the effect of improving the rigidity of the blended material when used for filling; ③ The 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative is a long-chain compound, and the structure contains an epoxy group ( ) or ethoxy (-0CH2CH3) or hydroxyl (-OH). When used for modification, the long chain is entangled with the modified base material, and the epoxy group ( ) or ethoxy (-0CH2CH3) or hydroxyl (-OH) can also participate in the reaction of the hydroxyl (-OH) on the surface of the heavy calcium carbonate under processing conditions or participate in the combination with the matrix material when the chain of the easily broken plastic matrix material is broken, thereby helping to improve the performance; ④ The 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative is a long-chain compound. When used in an adhesive, the long chain is swollen to form an intertwined structure, which helps to improve the thixotropy of the blending system. When the tung oil polyol-based 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative is used, the hydroxyl (-OH) also has the ability to form a network structure through hydrogen bonds.

[0097] The rosmarinic acid and its derivatives are one of rosmarinic acid dodecanol ester, rosmarinic acid methyl ester or rosmarinic acid. ① The rosmarinic acid and its derivatives have a unique fragrance and can improve the odor of the applied plastic matrix material; ② Studies have shown that the rosmarinic acid and its derivatives can change the permeability of bacterial cell membranes, leading to the leakage of reducing sugars and proteins, affecting the cell metabolism process and inhibiting the activity of polymerase, thereby inhibiting the replication process of bacterial DNA; ③ Studies have shown that the rosmarinic acid and its derivatives have antioxidant effects, and their antioxidant effects are related to their structures. The ortho-diphenolic hydroxyl group is the material basis for the free radical scavenging activity, and the conjugated double bond at the C3 position has a synergistic effect; ④ The rosmarinic acid ⑤ The rosmarinic acid and its derivatives contain a large number of highly active hydroxyl groups (-OH) or methoxy groups (-OCH3), which make it possible to react with the hydroxyl groups (-OH) on the surface of the heavy calcium carbonate, and to combine with the matrix material when the chain breaks with the easily broken plastic matrix material; ⑤ The rosmarinic acid and its derivatives contain a large number of hydroxyl groups (-OH), which have the ability to hydrogen bond the network structure when used in adhesives; ⑥ The rigid benzene ring structure contained in the rosmarinic acid and its derivatives also provides the possibility of improving the rigidity of the plastic blend material filled with the modified multifunctional heavy calcium carbonate.

[0098] The chitosan / chitosan oligosaccharide derivative is chitosan o-oxy (meta-oxy or para-oxy) benzaldehyde Schiff base-polyamine ethyl-diethyl phosphate or chitosan oligosaccharide o-oxy benzaldehyde Schiff base-polyamine ethyl-diethyl phosphate.

[0099] The mechanism of action of the chitosan / oligochitosan derivatives is as follows: ① The chitosan / oligochitosan derivatives have good antibacterial activity and can inhibit the growth and reproduction of some fungi and bacteria. The reasons are: first, the structure has polycations, which are easy to electrostatically interact with the negatively charged groups on the surface of fungi and bacteria, thereby changing the fluidity and permeability of the cell membrane, blocking nutrients from entering the cell and causing bacterial death, or damaging the integrity of the cell wall so that the cell wall tends to dissolve, causing the leakage of intracellular proteins and other cell components, and promoting cell apoptosis; second, chitosan and its derivatives can penetrate into the nucleus of bacteria and bind to DNA, interfere with DNA replication and transcription, inhibit the synthesis of mRNA, and achieve antibacterial effects; third, chitosan has a strong ability to bind metals. Chitosan and its derivatives chelate with metal ions, inhibit the uptake of trace elements by microorganisms, and bind to nutrients necessary for microbial growth, thereby achieving an inhibitory effect on microorganisms.

[0100] ② The chitosan / oligosaccharide derivative has a phosphorus (P) content of 0.012% (0.038% or 0.058%) and a nitrogen (N) content of 6.52% (6.45% or 7.03%) in the chitosan ortho-oxy (meta-oxy or para-oxy) benzaldehyde Schiff base-polyamine ethyl-diethyl phosphate structure, and a phosphorus (P) content of 1.21% and a nitrogen (N) content of 7.65% in the chitosan ortho-oxy (meta-oxy or para-oxy) benzaldehyde Schiff base-polyamine ethyl-diethyl phosphate structure, and both the chitosan ortho-oxy (meta-oxy or para-oxy) benzaldehyde Schiff base-polyamine ethyl-diethyl phosphate and the chitosan ortho-oxy benzaldehyde Schiff base-polyamine ethyl-diethyl phosphate contain a benzene ring structure with a carbon-forming function, and phosphorus (P) and nitrogen (N) are flame retardant elements of flame retardants, and have a synergistic effect with halogen flame retardants, and therefore have a flame retardant synergistic effect.

[0101] ③ The chitosan / chitosan oligosaccharide derivative is a long-chain compound containing highly active ethoxy groups (-OCH2CH3), double bonds, imino groups (-NH-), and hydroxyl groups (-OH), which endows the compound with the ability to combine with the surface hydroxyl groups (-OH) of the heavy calcium carbonate under processing conditions, to entangle with the matrix resin in the blended material, and to combine with the matrix material when the chain of the easily broken matrix material breaks. Similarly, the compound has a rigid benzene ring structure, which helps to improve the performance of the blended material. At the same time, the presence of imino groups (-NH-), hydroxyl groups (-OH) and long-chain structures helps to form a network structure in the adhesive, which is beneficial to the thixotropy of the adhesive.

[0102] The titanium dioxide is rutile nano titanium dioxide. The mechanism of action of the titanium dioxide is as follows: ① UV protection mechanism. The electronic structure of nano titanium dioxide is characterized by a full TiO2 valence band, an empty conduction band valence electron band, and a conduction band formed by an empty orbit. When it is irradiated with ultraviolet rays, light with energy greater than the width of its valence band (about 2.3eV) is absorbed, so that the electrons in the valence band are excited to the conduction band, resulting in a lack of valence electron bands and holes, forming electron-hole pairs that are easy to move and highly active. Such electron-hole pairs can, on the one hand, recombine with each other when various redox reactions occur, releasing energy in the form of heat or fluorescence; on the other hand, they can be dissociated into free holes and free electrons that freely migrate in the lattice to the lattice surface or other reaction sites, and are immediately captured by surface groups. When the particle size of nano titanium dioxide is large, the shielding of ultraviolet rays is mainly based on reflection and scattering. As the particle size decreases, light can pass through the particle surface of titanium dioxide, and the electrons on the valence band absorb ultraviolet rays and are excited to the conduction band, while generating electron-hole pairs. The mechanism is mainly the absorption of ultraviolet rays; ② Antibacterial mechanism. Under normal circumstances, titanium dioxide will activate surface water to produce surface hydroxyl groups to capture free holes and form hydroxyl radicals. The free electrons will quickly combine with the absorbed oxygen to produce superoxide radicals. The generated superoxide radicals react with most organic matter, and can also react with organic matter in microorganisms, ultimately leading to the decomposition of microorganisms.

[0103] Based on the above analysis: ① The use of the coupling agent allows the bipolar active groups in the coupling agent to chemically or physically combine with the hydroxyl groups (-OH) on the surface of the heavy calcium carbonate, and at the same time, cooperate with the hydroxyl groups (-OH) contained in the α-linolenic acid polyhydroxy derivative to participate in the reaction of the hydroxyl groups (-OH) on the surface of the heavy calcium carbonate. The film-forming function of the aluminate coupling agent in the coupling agent on the surface of calcium carbonate or the rapid change of the surface energy of the titanate coupling agent in the coupling agent due to the large number of carbon atoms, greatly reducing the viscosity of the system and the α-linolenic acid polyhydroxy derivative separating the molecular distance, effectively reducing the viscosity of the filling system when the modified multifunctional heavy calcium carbonate is applied. .

[0104] ② The tung oil polyol-based 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives in the α-linolenic acid polyhydroxy derivatives, the rosmarinic acid and its derivatives, the chitosan / chitosan oligosaccharide derivatives and the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives all contain polyhydroxyl groups (-OH) or amine groups (-NH2) or imino groups (-NH-), respectively. The α-linolenic acid polyhydroxy derivatives, the chitosan / chitosan oligosaccharide derivatives and the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives are long-chain compounds. When they are used for adhesive filling, the α-linolenic acid polyhydroxy derivatives, the chitosan / chitosan oligosaccharide derivatives, the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives are The long chains of the 10-oxide derivatives are swollen, and the swollen long chains are entangled with each other. When the hydroxyl (-OH) or amine (-NH2) or imino (-NH-) on the structure of the tung oil polyol-based 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives in the α-linolenic acid polyhydroxy derivatives, the rosmarinic acid and its derivatives, the chitosan / chitosan oligosaccharide derivatives and the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives are dissolved in an organic system, they are gelled due to the action of hydrogen bonds to form a thixotropic network structure. These network structures or the entangled long chains are destroyed under the action of shear force, which is manifested as a decrease in viscosity, so that the system recovers good fluidity. When the shear force is eliminated, the three-dimensional structure will recover by itself to increase the viscosity, showing thixotropy.

[0105] ③ The phosphorus (P), nitrogen (N) or silicon (Si) contained in the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative and the chitosan / chitosan oligosaccharide derivative respectively are components of the flame retardant, and the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, the chitosan / chitosan oligosaccharide derivative and the rosmarinic acid and its derivatives all contain a benzene ring structure that can form carbon, and phosphorus (P) and nitrogen (N) are also synergists of halogen element flame retardants. The coupling agent contains aluminum (Al) and phosphorus (P) with flame retardant effects, which helps to reduce the overall cost of the formula when designing a flame retardant material formula filled with the modified multifunctional heavy calcium carbonate.

[0106] ④ The rosmarinic acid and its derivatives, the chitosan / chitosan oligosaccharide derivatives and the titanium dioxide all have antibacterial function. The combination of the three makes the polymer material filled with the modified multifunctional heavy calcium carbonate have antibacterial properties.

[0107] ⑤ The rosmarinic acid and its derivatives and the titanium dioxide both have antioxidant effects. The combination of the two improves the aging resistance of the polymer material filled with the modified multifunctional heavy calcium carbonate.

[0108] ⑥ The α-linolenic acid polyhydroxy derivative, the chitosan / chitosan oligosaccharide derivative, and the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative are long-chain compounds. When the modified calcium carbonate is used for filling, the long-chain structures of the α-linolenic acid polyhydroxy derivative, the chitosan / chitosan oligosaccharide derivative, and the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative are entangled with the matrix material, wherein the α-linolenic acid polyhydroxy derivative contains a hydroxyl group (-OH), the chitosan / chitosan oligosaccharide derivative contains an ethoxy group (-OCH2CH3), and the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative contains a hydroxyl group (-OH) or an ethoxy group (-OCH2CH3) or an epoxy group (-OCH2CH3) ), the rosmarinic acid and its derivatives contain hydroxyl (-OH) and / or methoxy (-OCH3) in their structures, and the hydroxyl (-OH), methoxy (-OCH3), ethoxy (-OCH2CH3) or epoxy ( ) can produce a grafting or cross-linking reaction with the matrix material when conditions permit, and the use of the coupling agent helps to improve the mechanical properties of the modified multifunctional heavy calcium carbonate filling system.

[0109] ⑦ The chitosan / oligochitosan derivatives, the rosmarinic acid and its derivatives, and the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives all contain rigid benzene rings, which, when combined with inorganic rigid particle calcium carbonate, help improve the rigidity of the modified multifunctional heavy calcium carbonate filling system.

[0110] ⑧ The rosmarinic acid and its derivatives have a special fragrance, which helps to improve the smell of the multifunctional heavy calcium carbonate filling system using this modification.

[0111] like Figures 1 to 4 As shown, the present embodiment also relates to a method for preparing the modified multifunctional heavy carbonate, which is completed by using a weightless mixer 7, an auxiliary agent conveying system and a three-roller activation unit 9, wherein a raw material feeding port 4 and an auxiliary agent feeding port 5 are provided at the top of the weightless mixer 7, a discharge port is provided at the middle position of the bottom of the weightless mixer 7, a discharge motor is installed on the discharge port, and the discharge motor is connected to the auger 8 at the bottom.

[0112] The auxiliary agent delivery system includes a liquid auxiliary agent delivery system and a solid auxiliary agent delivery system. The liquid auxiliary agent delivery system includes a heating tank 21, a heating pipe 29 is installed in the heating tank 21, a liquid discharge pipe is installed near the bottom of the outer side of the heating tank 21, the liquid discharge pipe is connected to the liquid inlet pipe of the metering pump 22, the liquid outlet pipe of the metering pump 22 is connected to the liquid infusion pipe 23, the other end of the liquid infusion pipe 23 is connected to the nozzle rod 24, the other end of the nozzle rod 24 is installed with a nozzle 25, the nozzle rod 24 is connected to the auxiliary agent addition port 5, and the nozzle 25 is in the zero-gravity mixer 7; The liquid auxiliary agent delivery system also includes a heating tank 26, in which a heating tube similar to the heating tube 29 is installed, and a discharge pipe is installed on one side of the outer side of the heating tank 26 near the bottom, and the discharge pipe is connected to the liquid inlet pipe of the metering pump 27, and the liquid outlet pipe of the metering pump 27 is connected to the infusion pipe 28, and the other end of the infusion pipe 28 is connected to a nozzle rod similar to the nozzle rod 24, and the other end of the nozzle rod is installed with a nozzle similar to the nozzle 25, and the nozzle rod is connected to the auxiliary agent addition port 5 opened on the weightless mixer 7, and the nozzle is in the weightless mixer 7.

[0113] The solid additive delivery system includes a variable frequency high-speed mixer 19, a buffer bin 20 is installed below the discharge port of the variable frequency high-speed mixer 19, and a loss-in-weight scale 3 is installed below the discharge port of the buffer bin 20. Specifically, the loss-in-weight scale 3 includes a bin and a barrel placed below the bin, a screw is installed in the barrel, the rear end of the screw extends out of the barrel and is connected to a power system, a discharge port is installed at the front end of the barrel, and the bin is connected to the discharge port of the buffer bin 20.

[0114] The three-roller activation unit 9 includes an elevator 2, the discharge port of the weightless mixer 7 is connected to the feed port of the elevator 2 through an auger 2 8, the discharge port of the elevator 2 is connected to a raw material bin 1, a discharge port is provided in the middle of the bottom of the raw material bin 1, a discharge motor is installed below the discharge port, an auger 6 is installed below the discharge motor, the discharge port of the auger 6 is connected to the three-roller activation unit 9, and the discharge port of the loss-in-weight scale 3 is connected to the auger 6.

[0115] The three-roller activation unit 9 includes a first three-roller activation machine 901 connected to the discharge port of the auger 6, a second three-roller activation machine 902 connected to the discharge port of the first three-roller activation machine 901, and a third three-roller activation machine 903 connected to the discharge port of the second three-roller activation machine 902. The discharge port of the third three-roller activation machine 903 is connected to the air inlet of the induced draft fan 10. The air outlet of the induced draft fan 10 is connected to the feed port of the classifier 13 through the pipeline 11. In addition to the feed port, the classifier 13 is also provided with upper and lower discharge ports. The lower The discharge port is connected to the auger 1 6 through a pipe 2 12, and is located near the discharge port of the auger 1 6. The upper discharge port of the classifier 13 is connected to the bag filter 15 through a pipe 4 30. A discharge port is provided in the middle of the bottom of the bag filter 15. A discharge motor is connected to the discharge port. An air lock 16 is connected below the discharge motor. A pipe 3 17 is connected below the air lock 16. One end of the pipe 3 17 is connected to a Roots blower 14, and the other end is connected to a finished product bin 18. A discharge port is provided in the middle of the bottom of the finished product bin 18, and a discharge motor is installed below the discharge port.

[0116] Therefore: the preparation steps of the modified multifunctional calcium carbonate are as follows:

[0117] SP B1 , raise the temperature of the zero-gravity mixer 7 to 80-90° C., and keep it warm for 30 minutes after reaching the set temperature.

[0118] SP B2 , add the coupling agent into one of the heating tanks, when the coupling agent is liquid and the kinematic viscosity at 25°C is not greater than 80 mm 2 / s, no heating is required, when the kinematic viscosity at 25℃ is greater than 80mm 2 / s, the liquid coupling agent needs to be heated to reduce viscosity, and the heating temperature is controlled at a heating temperature at which the kinematic viscosity of the liquid coupling agent is between 50 and 80 mm 2 / s; when the coupling agent is solid, the solid coupling agent needs to be heated to melt and reduce viscosity, and the heating temperature is controlled at a heating temperature at which the kinematic viscosity of the solid coupling agent after melting is 50~80mm 2 / s;

[0119] SP B3 , add the α-linolenic acid polyhydroxy derivative into the heating tank 26, and heat the heating tank at a temperature of 70 to 85°C.

[0120] SP B4, the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, the rosmarinic acid and its derivatives, the chitosan o-oxybenzaldehyde Schiff base-polyamine ethyl-diethyl phosphate, and the titanium dioxide are weighed according to the proportion of each component in the formula, and are put into the variable frequency high-speed mixer 19 to form a mixed solid additive, and 5 times the total amount of the mixed solid additive is added through step SP A8 The prepared heavy calcium carbonate is used to amplify the mass of mixed solid additives.

[0121] SP B5 , start the variable frequency high-speed mixer 19 to mix the materials. The frequency of the variable frequency high-speed mixer 19 is 10-12.5 Hz. After mixing for 5-7 minutes, adjust its frequency to 25-27 Hz. Continue mixing for 2-3 minutes and then discharge the materials. Discharge the enlarged auxiliary agent into the buffer bin, and put it into the silo on the loss-in-weight scale 3 through the buffer bin 20.

[0122] In the process of modifying the heavy calcium carbonate, as the amount of the mixing aid is consumed, the variable frequency high mixer 19 needs to transfer the mixed solid aid to the silo of the loss-in-weight scale 3 for replenishment. The purpose of the buffer bin 20 is to prevent the impact on the loss-in-weight scale 3 when the material is discharged directly from the variable frequency high mixer 19, thereby avoiding affecting the metering accuracy of the loss-in-weight scale 3. The purpose of using the heavy calcium carbonate to amplify the mixed solid aid is to increase its addition amount, facilitate the addition control of the loss-in-weight scale 3, and further ensure the addition accuracy of the aid.

[0123] SP B6 , start the zero-gravity mixer 7, and pass step SP A8 The prepared heavy calcium carbonate is metered into the zero-gravity mixer 7, and the rotation speed of the zero-gravity mixer 7 is adjusted to 50-70 rad / min.

[0124] SP B7 After the temperature of the heavy calcium carbonate material in the zero-gravity mixer 7 reaches 80°C, start the metering pump 22 corresponding to the heating tank 21 with a coupling agent built in. The coupling agent is sprayed onto the calcium carbonate material in the zero-gravity mixer 7 from the heating tank 21 through the metering pump 22, the infusion tube 23, the nozzle rod 24, and the nozzle 25. Adjust the output of the metering pump 22 to spray the coupling agent that matches the mass of the heavy calcium carbonate onto the heavy calcium carbonate material in the zero-gravity mixer 7. The coupling agent addition time is controlled to be completed within 45 to 60 seconds, and continue mixing for 10 to 12 minutes.

[0125] SP B8, start the metering pump 27 corresponding to the heating tank 26 containing the α-linolenic acid polyhydroxy derivative, and the α-linolenic acid polyhydroxy derivative is sprayed from the heating tank 26 through the metering pump 27, the infusion tube 28, the nozzle rod, and the nozzle onto the calcium carbonate material in the zero-gravity mixer 7. Adjust the output of the metering pump 27 to spray the α-linolenic acid polyhydroxy derivative matching the mass of the heavy calcium carbonate onto the heavy calcium carbonate material in the zero-gravity mixer 7. The addition time of the α-linolenic acid polyhydroxy derivative is controlled to be completed within 45 to 60 seconds, and continue mixing for 20 to 25 minutes.

[0126] The purpose of adding the coupling agent and the α-linolenic acid polyhydroxy derivative at a time difference of 10 to 12 minutes is to ensure that the coupling agent combines with as many hydroxyl groups (-OH) on the surface of calcium carbonate as possible to reduce the hydroxyl (-OH) consumption of the α-linolenic acid polyhydroxy derivative.

[0127] SP B9 , start the discharge motor of the discharge port at the bottom of the weightless mixer 7, discharge the heavy calcium carbonate mixture containing the coupling agent and the α-linolenic acid polyhydroxy derivative, put it into the auger 2 8, start the auger 2 8, send the heavy calcium carbonate mixture into the elevator 2 through the auger 2 8, and start the elevator 2 to transfer the material to the raw material warehouse 1.

[0128] SP B10 , start the discharge motor installed at the bottom of the raw material bin 1 and the auger 6 below the discharge motor, so that the heavy calcium carbonate mixture material is quantitatively transferred from the raw material bin 1 to the auger 6.

[0129] SP B11 After starting the auger 6, start the loss-in-weight scale 3, and feed the mixed solid additives magnified by the heavy calcium carbonate into the auger 6 in proportion to the mass of the material transported by the auger 6, and mix them with the heavy calcium carbonate mixed material transferred from the raw material bin 1 to form a final mixed material.

[0130] SP B12 , start the three-roller activation unit 9, the auger 6 delivers the final mixed material into the three-roller activation unit 9 through the discharge port for continuous mixing and activation, that is, the final mixed material is mixed by the first three-roller activator 901 and then enters the second three-roller activator 902, and then enters the third three-roller activator 903. The final mixed material is continuously mixed and activated by the first three-roller activator 901, the second three-roller activator 902, and the third three-roller activator 903.

[0131] SPB13 , start the induced draft fan 10, and the final mixed material continuously mixed and activated by the three-roller activation unit 9 enters the classifier 13 through the pipeline 11 under the action of the induced draft fan 10.

[0132] SP B14 The mixed and activated mixed materials entering the classifier 13 are classified, and qualified powders enter the bag filter 15 from the upper discharge port of the classifier 13 through the pipeline 4 30. The powders agglomerated during the activation process enter the auger 1 6 from the lower discharge port of the classifier 13 through the pipeline 2 12, and return to the three-roller activation unit 9 for further activation and crushing. A cooling system is provided in the bag filter 15 to cool the mixed and activated materials.

[0133] SP B15 After the mixed and activated mixed material entering the bag filter 15 is cooled, the discharge motor installed at the bottom of the bag filter 15 and the air lock 16 below the discharge motor are started, and the qualified mixed and activated powder in the bag filter 15 enters the pipeline three 17 to start the Roots blower 14, and the mixed and activated powder enters the finished product warehouse 18 through the pipeline three 17.

[0134] SP B16 , packaging the materials in the finished product bin 18 to form a modified multifunctional calcium carbonate finished product.

[0135] In the following embodiments, ① the heavy calcium carbonate powder is selected from a particle size of D 50 =3.920µm, D 97 =12.614µm coarse powder, particle size D 50 =3.157µm, D 97 =9.753µm fine powder and particle size D 50 =2.139µm, D 97 =8.586µm ultrafine powder. 50 =3.920µm, D 97 =12.614µm heavy calcium carbonate is ground with sodium hexametaphosphate as the dispersant. 50 =3.157µm, D 97 =9.753µm heavy calcium carbonate is ground using sodium dodecyl sulfate as a dispersant. 50 =2.139µm, D 97 =8.586µm heavy calcium carbonate is ground to powder using a grinding aid dispersant of maleic acid-acrylic acid copolymer sodium salt.

[0136] ② The coupling agent is selected from phosphate acyloxy isooctyl aluminate or di(dioctyl pyrophosphoryloxy)hydroxyacetate titanate.

[0137] ③ The rosmarinic acid and its derivatives are selected from rosmarinic acid dodecanol ester.

[0138] ④ The chitosan / chitosan oligosaccharide derivative is chitosan o-oxybenzaldehyde Schiff base-polyamine ethyl-diethyl phosphate.

[0139] Example 1

[0140] Particle size D 50 =3.920µm, D 97 =12.614µm calcium carbonate 100 parts, phosphate acyloxy isooctyl aluminate 0.3 parts, α-linolenic acid polyhydroxy derivative 0.4 parts, R1 structure is,

[0141] , 0.5 parts of epoxy 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, 0.05 parts of rosmarinic acid dodecanol ester, 0.2 parts of chitosan o-oxybenzaldehyde Schiff base-polyamineethyl-diethyl phosphate, and 0.2 parts of titanium dioxide.

[0142] Example 2

[0143] Particle size D 50 =3.157µm, D 97 = 9.753µm calcium carbonate 100 parts, phosphate acyloxy isooctyl aluminate 0.4 parts, α-linolenic acid polyhydroxy derivative 0.6 parts, R1 structure is

[0144] , 0.8 parts of epoxy 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, 0.1 parts of rosmarinic acid dodecanol ester, 0.3 parts of chitosan o-oxybenzaldehyde Schiff base-polyamineethyl-diethyl phosphate, and 0.25 parts of titanium dioxide.

[0145] Example 3

[0146] Particle size D 50 =2.139µm, D 97 = 8.586µm calcium carbonate 100 parts, phosphate acyloxy isooctyl aluminate 0.5 parts, α-linolenic acid polyhydroxy derivative 0.7 parts, R1 structure is

[0147] , 1.0 part of epoxy 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, 0.15 part of rosmarinic acid dodecanol ester, 0.35 part of chitosan o-oxybenzaldehyde Schiff base-polyamineethyl-diethyl phosphate, and 0.3 part of titanium dioxide.

[0148] Example 4

[0149] Particle size D 50 =2.139µm, D 97 = 8.586µm calcium carbonate 100 parts, phosphate acyloxy isooctyl aluminate 0.5 parts, α-linolenic acid polyhydroxy derivative 0.7 parts, R1 structure is

[0150] , 1.0 part of epoxy 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, 0.15 part of rosmarinic acid dodecanol ester, 0.35 part of chitosan o-oxybenzaldehyde Schiff base-polyamineethyl-diethyl phosphate, and 0.3 part of titanium dioxide.

[0151] Example 5

[0152] Particle size D 50 =2.139µm, D 97 = 8.586µm calcium carbonate 100 parts, phosphate acyloxy isooctyl aluminate 0.5 parts, α-linolenic acid polyhydroxy derivative 0.7 parts, R1 structure is

[0153] , 1.0 part of epoxy 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, 0.15 part of rosmarinic acid dodecanol ester, 0.35 part of chitosan o-oxybenzaldehyde Schiff base-polyamineethyl-diethyl phosphate, and 0.3 part of titanium dioxide.

[0154] Example 6

[0155] Particle size D 50 =2.139µm, D 97 = 8.586µm calcium carbonate 100 parts, phosphate acyloxy isooctyl aluminate 0.5 parts, α-linolenic acid polyhydroxy derivative 0.7 parts, R1 structure is

[0156] , 1.0 part of tung oil polyol-based 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, 0.15 part of rosmarinic acid dodecanol ester, 0.35 part of chitosan o-oxybenzaldehyde Schiff base-polyamineethyl-diethyl phosphate, and 0.3 part of titanium dioxide.

[0157] Example 7

[0158] Particle size D 50 =2.139µm, D 97 = 8.586µm calcium carbonate 100 parts, phosphate acyloxy isooctyl aluminate 0.5 parts, α-linolenic acid polyhydroxy derivative 0.7 parts, R1 structure is

[0159] , 1.0 part of siloxane 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, 0.15 part of rosmarinic acid dodecanol ester, 0.35 part of chitosan o-oxybenzaldehyde Schiff base-polyamineethyl-diethyl phosphate, and 0.3 part of titanium dioxide.

[0160] Example 8

[0161] Particle size D 50 =2.139µm, D 97 = 8.586µm calcium carbonate 100 parts, phosphate acyloxy isooctyl aluminate 0.3 parts, α-linolenic acid polyhydroxy derivative 0.7 parts, R1 structure is

[0162] , 0.5 parts of epoxy 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, 0.15 parts of rosmarinic acid dodecanol ester, 0.2 parts of chitosan o-oxybenzaldehyde Schiff base-polyamineethyl-diethyl phosphate, and 0.3 parts of titanium dioxide.

[0163] Example 9

[0164] Particle size D 50 =2.139µm, D 97 = 8.586µm calcium carbonate 100 parts, phosphate acyloxy isooctyl aluminate 0.4 parts, α-linolenic acid polyhydroxy derivative 0.6 parts, R1 structure is

[0165] , 0.8 parts of epoxy 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, 0.15 parts of rosmarinic acid dodecanol ester, 0.35 parts of chitosan o-oxybenzaldehyde Schiff base-polyamineethyl-diethyl phosphate, and 0.2 parts of titanium dioxide.

[0166] Example 10

[0167] Particle size D 50 =2.139µm, D 97 = 8.586µm calcium carbonate 100 parts, phosphate acyloxy isooctyl aluminate 0.3 parts, α-linolenic acid polyhydroxy derivative 0.4 parts, R1 structure is

[0168] , 0.5 parts of epoxy 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, 0.05 parts of rosmarinic acid dodecanol ester, 0.2 parts of chitosan o-oxybenzaldehyde Schiff base-polyamineethyl-diethyl phosphate, and 0.2 parts of titanium dioxide.

[0169] Embodiment 11

[0170] Particle size D 50 =2.139µm, D 97 = 8.586µm calcium carbonate 100 parts, di (dioctyl pyrophosphoryloxy) glycolate titanate 0.5 parts, α-linolenic acid polyhydroxy derivative 0.7 parts, R1 structure is

[0171] , 1.0 part of epoxy 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, 0.15 part of rosmarinic acid dodecanol ester, 0.35 part of chitosan o-oxybenzaldehyde Schiff base-polyamineethyl-diethyl phosphate, and 0.3 part of titanium dioxide.

[0172] Comparative Example 1:

[0173] Particle size D 50 =3.920µm, D 97 =12.614µm calcium carbonate 100 parts, phosphate acyloxy isooctyl aluminate 0.5 parts.

[0174] Comparative Example 2

[0175] Particle size D 50 =3.157µm, D 97 =9.753µm 100 parts of calcium carbonate, 0.7 parts of phosphate acyloxy isooctyl aluminate.

[0176] Comparative Example 3

[0177] Particle size D 50 =2.139µm, D 97 =8.586µm 100 parts of calcium carbonate, 1.0 parts of phosphate acyloxy isooctyl aluminate.

[0178] The comparison of oil absorption value, activation degree and blue light whiteness of Examples 1 to 11 and Comparative Examples 1 to 3 is shown in Table 1 and Table 2. 50 =3.920µm, D 97 =12.614µm The blue light whiteness of calcium carbonate raw powder is 93.1%, and the particle size is D 50 =3.157µm, D 97 =9.753µm The blue light whiteness of calcium carbonate raw powder is 94.3%, and the particle size is D 50 =2.139µm, D 97 =8.586µm The whiteness of the pale blue light of calcium carbonate is 94.8%.

[0179] Table 1 Test data of Examples 1 to 7

[0180]

[0181] Table 2 Test data of Examples 8 to 11 and Comparative Examples 1 to 3

[0182]

[0183] It can be seen from Table 1 and Table 2 that compared with Comparative Example 1, Example 2 and Comparative Example 2, and Examples 3 to 11 and Comparative Example 3, Example 1 has a lower oil absorption value, a higher activation degree, and a higher whiteness. Moreover, Examples 1 to 11 have less effect on the whiteness of the original powder than Comparative Examples 1 to 3, indicating that the surface modification effect of the composite additive of the present invention on the calcium carbonate powder is more obvious than the modification effect of a single coupling agent.

[0184] In terms of the overall effect, the trends of the filling application effects of Examples 1 to 11 are consistent. For the sake of simplicity of description, the present invention uses the modified calcium carbonate of Example 3 as a practical example to illustrate the application effect of the present invention, and uses the practical example of the modified calcium carbonate of Comparative Example 3 as a comparative example.

[0185] Example 3-1

[0186] Homopolymer PP (polypropylene) 52 parts, copolymer PP 10 parts, modified calcium carbonate prepared by Example 3 25 parts, HDPE (high-density polyethylene) 5 parts, POE (ethylene-octene copolymer) 8 parts, 1010 (tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester) 0.25 parts, 168 (tris[2.4-di-tert-butylphenyl] phosphite) 0.3 parts, polyethylene wax 0.15 parts, calcium stearate.

[0187] Comparative Example 3-1

[0188] 52 parts of homopolymer PP, 10 parts of copolymer PP, 25 parts of modified calcium carbonate prepared by Comparative Example 3, 5 parts of HDPE (high-density polyethylene), 8 parts of POE (ethylene-octene copolymer), 0.25 parts of 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), 0.25 parts of 168 tris[2.4-di-tert-butylphenyl] phosphite), 0.3 parts of polyethylene wax, and 0.15 parts of calcium stearate.

[0189] The materials of Example 3-1 and Comparative Example 3-1 were weighed according to the formula ratio, put into a high-speed mixer and mixed at 80-85°C for 3-5 minutes, and the mixed materials were granulated by a twin-screw granulator, the aspect ratio of the twin screw was 44 / 1, and the granulation temperature was 195°C-235°C. The granulated materials were dried in an oven at 80-90°C for 2h and then injection molded into specimens, the injection molding temperature was 190-230°C, and the specimens were placed at 23±2°C and 50±5% humidity for 24h before testing. The test data are shown in Table 3.

[0190] Table 3 Test data of Example 3-1 and Comparative Example 3-1 filled with PP

[0191]

[0192] Example 3-1 and comparative example 3-1 were injection molded into 60×60×1 mm specimens respectively. The surfaces of the specimens were cleaned with anhydrous ethanol, dried, placed in a container holder filled with distilled water, placed in a constant temperature box at 80±2°C for 2h±10min, taken out, cooled to 60±5°C, and then smelled. The results are shown in Table 4.

[0193] Table 4 Odor test results of Example 3-1 and Comparative Example 3-1 filled with PP

[0194]

[0195] Example 3-2

[0196] PBT (polybutylene terephthalate) 55.5 parts, brominated epoxy resin 9 parts, Sb2O3 (antimony trioxide) 2.5 parts, compatibilizer 3 parts, modified calcium carbonate prepared in Example 3 30 parts, PETs (pentaerythritol stearate) 0.21 parts, 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl ester) 0.15 parts, 168 tris [2.4-di-tert-butylphenyl] phosphite) 0.15 parts.

[0197] Comparative Example 3-2

[0198] PBT 52 parts, brominated epoxy resin 12 parts, Sb2O3 3 parts, compatibilizer 3 parts, modified calcium carbonate prepared in Comparative Example 3 30 parts, PETs (pentaerythritol stearate) 0.21 parts, 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester) 0.15 parts, 168 tris [2.4-di-tert-butylphenyl] phosphite) 0.15 parts.

[0199] The materials of Example 3-2 and Comparative Example 3-2 were weighed according to the formula ratio, put into a high-speed mixer and mixed at 100-105°C for 5-7 minutes, and the mixed materials were granulated by a twin-screw granulator, the aspect ratio of the twin screw was 44 / 1, and the granulation temperature was 200°C-235°C. The granulated materials were dried in an oven at 80-90°C for 2h and then injection molded into specimens, the injection molding temperature was 200-230°C, and the specimens were placed at 23±2°C and 50±5% humidity for 24h before testing. The test data are shown in Table 5.

[0200] Table 5 Test data of Example 3-2 and Comparative Example 3-2 filled and flame retardant PBT

[0201]

[0202] Example 3-3

[0203] Put 1047g of 107 glue and 47g of dimethyl silicone oil into a Z-type kneader, heat and stir for 30min, then add 1250g of modified calcium carbonate prepared in Example 3, heat to 110-120°C, evacuate to below -0.08MPa, stir for 3h, then vent, add 156g of white oil and stir for 30min, then cool to room temperature to form a base material. Under the protection of nitrogen, a part of the base material was sealed to prepare for the consistency test. 1000g of the base material was transferred to a double-shaft planetary mixer, 50g of methyl tributylacetoximate silane and 5g of vinyl tributylacetoximate silane were added, and the mixture was vacuumed and stirred for 30 minutes, with the vacuum degree kept below -0.08MPa. Then 0.6g of dibutyltin dilaurate, 2g of KH550 (3-aminopropyltriethoxysilane) and 2g of KH560 (γ-glycidyloxypropyltrimethoxysilane) were added, and the mixture was vacuumed and stirred for 25 minutes, and then squeezed into the rubber cylinder. The silicone rubber test was prepared.

[0204] Comparative Example 3-3

[0205] Put 1047g of 107 glue and 47g of dimethyl silicone oil into a Z-type kneader, heat and stir for 30min, then add 1250g of modified calcium carbonate prepared in Comparative Example 3, heat to 110-120°C, evacuate to below -0.08MPa, stir for 3h, then vent, add 156g of white oil and stir for 30min, cool to room temperature to form a base material, seal a part of the base material under nitrogen protection to prepare for consistency test, transfer 1000g of the base material to the Add 50g of methyl tributylidene silane and 5g of vinyl tributylidene silane to a double-shaft planetary mixer, and stir under vacuum for 30 minutes, keeping the vacuum degree below -0.08MPa. Then add 0.6g of dibutyltin dilaurate, 2g of KH550 (3-aminopropyltriethoxysilane), and 2g of KH560 (γ-glycidyloxypropyltrimethoxysilane), and continue to stir under vacuum for 25 minutes, and squeeze into the rubber cylinder. Prepare for silicone rubber testing.

[0206] The base material consistency, silicone adhesive extrusion, tensile properties, elongation at break, elastic recovery rate, and sag of Example 3-3 and Comparative Example 3-3 were tested respectively. The test results are shown in Table 6.

[0207] Table 6 Test data of Example 3-3 and Comparative Example 3-3

[0208]

[0209] Embodiment 3-4

[0210] PBAT (co-polymer of butylene adipate and butylene terephthalate) 64 parts, modified calcium carbonate prepared in Example 3 35 parts, BHA (tert-butyl-4-hydroxyanisole) 0.15 parts, BHT (2,6-di-tert-butyl-p-cresol) 0.15 parts, chain extender ADR-4368C 0.25 parts, polyethylene wax 0.3 parts, calcium stearate 0.15 parts.

[0211] Comparative Examples 3-4

[0212] 64 parts of PBAT, 35 parts of modified calcium carbonate prepared in Comparative Example 3, 0.15 parts of BHA (tert-butyl-4-hydroxyanisole), 0.15 parts of BHT (2,6-di-tert-butyl-p-cresol), 0.25 parts of chain extender ADR-4368C, 0.3 parts of polyethylene wax, and 0.15 parts of calcium stearate.

[0213] The materials of Example 3-4 and Comparative Example 3-4 were weighed according to the formula ratio, put into a high-speed mixer and mixed at 80-85°C for 3-5 minutes, and the mixed materials were granulated by a twin-screw granulator, the twin-screw aspect ratio was 44 / 1, and the granulation temperature was 80-165°C. The granulated materials were dried in an oven at 70-80°C for 2 hours and then blown into film, the film blowing temperature was 90-160°C, and the film thickness was 0.04mm. Part of the film was placed at 23±2℃ and 50±5% humidity for 24h and then cut into samples for mechanical properties testing. Part of the film was cut into 10×30mm and buried for 20cm to test antibacterial properties. Part of the film was naturally stored off the ground after bagging to test shelf life to test anti-aging properties. The antibacterial properties were judged by the appearance of holes in the film, and the shelf life was judged by a 50% decrease in elongation at break. The buried film was sampled and observed 50 days after being buried. The sampling cycle was 5 days, and the date when the holes were observed was recorded as the test day. The test started 200 days after the homemade film was tested, and the date when the elongation at break was less than 50% was recorded as the test day. The test data is shown in Table 7.

[0214] Table 7 Test data of Examples 3-4 and Comparative Examples 3-4

[0215]

[0216] As can be seen from Table 3, the tensile strength, impact strength, flexural strength, elongation at break, heat deformation temperature, hardness and melt index of Example 3-1 are all higher than those of Comparative Example 3-1. This is due to the dual effects of the α-linolenic acid polyhydroxy derivative, the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, and the long molecular chains of the chitosan / chitosan oligosaccharide derivative entangled with the PP substrate, and the benzene ring structure contained in the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, the rosmarinic acid derivative, and the chitosan / chitosan oligosaccharide derivative, in addition to the effect of the coupling agent.

[0217] It can be seen from Table 4 that the odor of Example 3-1 is significantly better than that of Comparative Example 3-1, indicating that the fragrant odor of rosmarinic acid and its derivatives can improve the odor of the blended material.

[0218] In Table 5, under the same flame retardant grade, after Example 3-2 was filled with flame retardant PBT, its tensile strength and impact strength were higher than those of Comparative Example 3-2, and the amount of flame retardant used in the Example was reduced by 23.3% compared with that in the Comparative Example. The reason is that on the one hand, the terminal carboxyl group (-COOH) of the undried PBT was hydrolyzed and broken at high temperature, and the hydroxyl group (-OH) or epoxy group (-OH) contained in the long molecular chain of the α-linolenic acid polyhydroxy derivative, the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, the rosmarinic acid derivative, and the chitosan / chitosan oligosaccharide derivative was ), methoxy (-OCH3), ethoxy (-OCH2CH3) react with the broken PBT chain, not only delaying or preventing the PBT from continuing to break, but also due to the hydroxyl (-OH) or epoxy ( ), methoxy (-OCH3), ethoxy (-OCH2CH3) reaction to extend the molecular chain; on the other hand, the benzene ring contained in the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, the rosmarinic acid derivative, and the chitosan / chitosan oligosaccharide derivative provides a certain rigidity; on the third aspect, the flame retardant elements aluminum (Al), phosphorus (P) contained in the coupling agent and the flame retardant elements phosphorus (P), nitrogen (N) or silicon (Si) in the structure of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, the rosmarinic acid derivative, and the chitosan / chitosan oligosaccharide derivative and the benzene ring with carbon-forming function contained in the structure of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, the rosmarinic acid derivative, and the chitosan / chitosan oligosaccharide derivative form a synergistic effect with the flame retardant in the blending system, thereby reducing the amount of flame retardant used.

[0219] The base material viscosity, finished adhesive extrusion, tensile strength, elongation at break and finished adhesive sag of Example 3-3 in Table 6 are significantly better than those of Comparative Example 3-3, and the sag of Comparative Example 3-3 can no longer meet the technical requirement of ≦3mm specified in GB / T 14683-2017 "Silicone and Modified Silicone Building Sealant". This is because the hydroxyl (-OH) or amine (-NH2) or imino (-NH-) in the α-linolenic acid polyhydroxy derivatives, the rosmarinic acid and its derivatives, and the chitosan / chitosan oligosaccharide derivatives described in Example 3-3, when dissolved in an organic system, gels due to hydrogen bonding to form a thixotropic network structure. At the same time, the α-linolenic acid polyhydroxy derivatives, the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives, and the chitosan / chitosan oligosaccharide derivatives all have long-chain structures, and the swollen long chains are entangled with each other. These network structures or entangled long chains are destroyed under the action of shear force, which is manifested as a decrease in viscosity and the system recovers good fluidity. When the shear force is eliminated, the three-dimensional structure will recover by itself to increase the viscosity, showing thixotropy, which is more conducive to the performance of filling silicone glue than calcium carbonate modified with a coupling agent alone.

[0220] As can be seen from Table 7, the tensile strength, elongation at break, time for the appearance of no holes in the buried ground and the shelf life of the bag making of Examples 3-4 are significantly higher than those of Comparative Examples 3-4. This is because during high temperature processing, the terminal hydroxyl group (-OH) of PBAT is thermally broken and reacts with the active group hydroxyl group (-OH) or epoxy group ( ), amine (-NH2), methoxy (-OCH3), and ethoxy (-OCH2CH3), thereby delaying or terminating the probability of PBAT chain scission. At the same time, the rosmarinic acid and its derivatives, the chitosan / oligochitosan derivatives, and the titanium dioxide all have antibacterial functions; the rosmarinic acid and its derivatives, and the titanium dioxide all have antioxidant effects, so the antibacterial and anti-aging abilities of the PBAT film are enhanced.

[0221] The description of the present invention is given for the purpose of illustration and description, and is not intended to be exhaustive or to limit the invention to the disclosed form. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for particular uses.

Claims

1. A modified multifunctional calcium carbonate, characterized in that: The invention comprises the following components in proportion by weight: 100 parts of calcium carbonate, 0.3-0.5 parts of coupling agent, 0.4-0.7 parts of α-linolenic acid polyhydroxy derivatives, 0.5-1.0 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives, 0.05-0.15 parts of rosmarinic acid and its derivatives, 0.2-0.35 parts of chitosan / chitosan oligosaccharide derivatives, and 0.2-0.3 parts of titanium dioxide; The particle size of the calcium carbonate measured by the OMEC particle size tester is D 50 ≦4.152µm, D 97 Heavy calcium carbonate ≦13.116µm; The 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative includes one of a 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing an epoxy group, a 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing a tung oil polyol group, or a 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing a siloxane group; Wherein, the structural formula of the epoxy-containing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative is: The structural formula of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing tung oil polyol group is , The structural formula of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative containing a siloxane group is 。 2. A modified multifunctional calcium carbonate as claimed in claim 1, characterized in that: The heavy calcium carbonate is obtained by grinding with a vertical mill; The heavy calcium carbonate is added with 1-1.5‰ grinding aid dispersant during grinding; The grinding aid dispersant is one of maleic acid-acrylic acid copolymer sodium salt, sodium dodecyl sulfate, and sodium hexametaphosphate; The obtaining of the heavy calcium carbonate comprises the following steps: SP A1 , using tap water to wash the calcium carbonate ore to remove the silt and humus in the calcium carbonate ore; SP A2 , crushing the calcium carbonate ore, and after the first and second crushing processes, the maximum size of the calcium carbonate ore after crushing is no more than 30 mm; SP A3 , take 20 to 25 times the mass of the grinding aid dispersant and add it to the grinding aid dispersant to prepare a dilute solution or emulsion, heat the grinding aid dispersant diluted with pure water, and control the heating temperature to 50 to 60° C.; SP A4 3. Metering and conveying the crushed calcium carbonate ore using a vibrating screen; SP A5 , using a metering pump to evenly spray the diluted and heated grinding aid dispersant onto the crushed calcium carbonate ore on the vibrating screen in a ratio that matches the mass of the calcium carbonate ore; SP A6 , feeding the calcium carbonate ore sprayed with the grinding aid dispersant into the vertical mill for grinding; SP A7 , setting the grinding process according to the particle size requirements of the heavy calcium carbonate to grind out powder that meets the particle size requirements; SP A8 2. If the powder that meets the particle size requirements needs to be further classified, it will be sent to the next classification procedure. After the powder that meets the specified requirements is classified, it will be sent to the finished product warehouse; powder that does not need to be further classified will be directly sent to the finished product warehouse.

3. A modified multifunctional calcium carbonate as claimed in claim 1, characterized in that: The coupling agent is one of distearoyloxy isopropyl aluminate, phosphate acyloxy isooctyl aluminate, anti-settling aluminate, isopropyl tris (dioctyl pyrophosphate acyloxy) titanate, di (dioctyl pyrophosphate acyloxy) glycolate titanate, di (dioctyl pyrophosphate acyloxy) oxoester titanate, aluminum-titanium composite coupling agent, aluminum zirconate coupling agent, or a combination of two of them in any ratio.

4. A modified multifunctional calcium carbonate as claimed in claim 1, characterized in that: The structural formula of the α-linolenic acid polyhydroxy derivative is as follows: The structure of R1 is: , or 。 5. A modified multifunctional calcium carbonate as claimed in claim 1, characterized in that: The rosmarinic acid and its derivatives are one of rosmarinic acid dodecanol ester, rosmarinic acid methyl ester or rosmarinic acid.

6. A modified multifunctional calcium carbonate as claimed in claim 1, characterized in that: The chitosan / chitosan oligosaccharide derivative is one of chitosan o-oxybenzaldehyde Schiff base-polyamine ethyl-diethyl phosphate, chitosan m-oxybenzaldehyde Schiff base-polyamine ethyl-diethyl phosphate, chitosan p-oxybenzaldehyde Schiff base-polyamine ethyl-diethyl phosphate, and chitosan oligosaccharide o-oxybenzaldehyde Schiff base-polyamine ethyl-diethyl phosphate.

7. A modified multifunctional calcium carbonate as claimed in claim 1, characterized in that: The titanium dioxide is rutile nano titanium dioxide.

8. The method for preparing a modified multifunctional calcium carbonate according to claim 2, wherein the method comprises: The auxiliary agent delivery system includes a liquid auxiliary agent delivery system and a solid auxiliary agent delivery system; The liquid auxiliary agent delivery system includes two heating tanks, each of which is connected to a metering pump, each of which is connected to a liquid infusion tube, the other end of which is connected to a nozzle rod, a nozzle is installed on the nozzle rod, the nozzle rod is installed on the zero-gravity mixer, and a heating tube is installed in the heating tank; The solid additive delivery system includes a variable frequency high-speed mixer and a buffer bin disposed below the discharge port of the variable frequency high-speed mixer, and a loss-in-weight scale is installed below the discharge port of the buffer bin; The loss-in-weight scale comprises a silo and a barrel placed below the silo, a screw is installed in the barrel, the rear end of the screw extends out of the barrel and is connected to a power system, a discharge port is installed at the front end of the barrel, and the silo is connected to the discharge port of the buffer silo; The three-roller activation unit includes an elevator, the discharge port of the weightless mixer is connected to the feed port of the elevator through auger 2, the discharge port of the elevator is connected to a raw material bin, the discharge port at the bottom of the raw material bin is connected to auger 1, the discharge port of the loss-in-weight scale is connected to auger 1, the discharge port of auger 1 is connected to the three-roller activator, the discharge port of the three-roller activator is connected to an induced draft fan, the discharge port of the induced draft fan is connected to a classifier through pipeline 1, the classifier is provided with upper and lower discharge ports, the upper discharge port of the classifier is connected to a bag filter through pipeline 4, the bag filter is connected to a corresponding finished product bin through pipeline 3 equipped with a Roots blower, and the lower discharge port of the classifier is connected to the auger 1 through pipeline 2.

9. The method for preparing the modified multifunctional calcium carbonate according to claim 8, characterized in that: The following steps are included: SP B1 , raising the temperature of the zero-gravity mixer to 80-90° C., and keeping the temperature for 30 minutes after reaching the set temperature; SP B2 , add the coupling agent into one of the heating tanks, when the coupling agent is liquid and the kinematic viscosity at 25°C is not greater than 80 mm 2 / s, no heating is required, when the kinematic viscosity at 25℃ is greater than 80mm 2 / s, the liquid coupling agent needs to be heated to reduce viscosity, and the heating temperature is controlled at a heating temperature at which the kinematic viscosity of the liquid coupling agent is between 50 and 80 mm 2 / s; when the coupling agent is solid, the solid coupling agent needs to be heated to melt and reduce viscosity, and the heating temperature is controlled at a heating temperature at which the kinematic viscosity of the solid coupling agent after melting is 50~80mm 2 / s; SP B3 , adding the α-linolenic acid polyhydroxy derivative into another heating tank, and heating the heating tank at a heating temperature of 70 to 85° C.; SP B4 , the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivative, the rosmarinic acid and its derivatives, the chitosan / chitosan oligosaccharide derivatives, and the titanium dioxide are weighed according to the proportion of each component in the formula, and are put into the variable frequency high-speed mixer to form a mixed solid additive, and 5 times the total amount of the mixed solid additive is added through step SP A8 The prepared heavy calcium carbonate is used to amplify the mass of the mixed solid additive; SP B5 , start the variable frequency high-speed mixer to mix materials, the frequency of the variable frequency high-speed mixer is 10-12.5 Hz, adjust its frequency to 25-27 Hz after mixing for 5-7 minutes, continue mixing for 2-3 minutes and then discharge the materials, discharge the enlarged auxiliary agent into the buffer bin, and put it into the silo on the loss-in-weight scale through the buffer bin; SP B6 , start the zero-gravity mixer, and pass step SP A8 The prepared heavy calcium carbonate is metered into the zero-gravity mixer, and the speed of the zero-gravity mixer is adjusted to 50-70 rad / min; SP B7 , after the temperature of the heavy calcium carbonate material in the zero-gravity mixer reaches 80° C., start the metering pump corresponding to the heating tank with a built-in coupling agent, adjust the output of the metering pump, and spray the coupling agent matching the mass of the heavy calcium carbonate onto the heavy calcium carbonate material in the zero-gravity mixer. The coupling agent addition time is controlled within 45 to 60 seconds, and the mixing is continued for 10 to 12 minutes; SP B8 , starting the metering pump corresponding to the heating tank containing the α-linolenic acid polyhydroxy derivative, adjusting the output of the metering pump, spraying the α-linolenic acid polyhydroxy derivative matching the mass of the heavy calcium carbonate onto the heavy calcium carbonate material in the zero-gravity mixer, controlling the addition time of the α-linolenic acid polyhydroxy derivative to be completed within 45 to 60 seconds, and continuing mixing for 20 to 25 minutes; SP B9 , discharging the heavy calcium carbonate mixture containing the coupling agent and the α-linolenic acid polyhydroxy derivative, and transferring it from the zero-gravity mixer to the raw material bin via the auger 2 and the elevator; SP B10 , starting the auger 1 to transfer the heavy calcium carbonate mixture from the raw material bin to the auger 1 in a quantitative manner; SP B11 , starting the loss-in-weight scale, feeding the mixed solid additives magnified by the heavy calcium carbonate into the auger according to a proportion, and mixing them with the heavy calcium carbonate mixed material transferred from the raw material bin to form a final mixed material; SP B12 , starting the three-roller activation unit, and the auger 1 delivers the final mixed material into the three-roller activation unit through the discharge port for continuous mixing and activation; SP B13 , starting the induced draft fan, and the final mixed material activated by the three-roller activation machine enters the classifier through pipeline 1 under the action of the induced draft fan; SP B14 , the mixed and activated mixed materials entering the classifier are classified, and the qualified powders enter the bag filter from the upper discharge port of the classifier through the pipeline 4, and the powders agglomerated during the activation process enter the auger 1 from the lower discharge port of the classifier through the pipeline 2, and return to the three-roller activation unit for further activation and crushing; SP B15 , the mixed and activated mixed material entering the bag filter is cooled and then enters the finished product bin through pipeline three; SP B16 , packaging the materials in the finished product warehouse to form a modified multifunctional calcium carbonate finished product.